2020
DOI: 10.11606/s1518-8787.2020054001695
|View full text |Cite
|
Sign up to set email alerts
|

Development of an instrument to measure the cultural competence of health care workers

Abstract: OBJECTIVE: To validate an instrument measuring the cultural competence in health care workers from Chile. METHODS: Using Sue & Sue’s theoretical model of cultural competence, we designed a scale, which was assessed by health care workers and experts. Subsequently, the scale was applied to a sample of 483 different health care workers, during 2018 in Santiago de Chile. The analysis included: exploratory and confirmatory factor analysis, estimation of reliability, and analysis of measurement bias. Finally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
(31 reference statements)
1
3
1
9
Order By: Relevance
“…There seems to be a need of studies comparing cultural competence between different healthcare professionals. This study reported significantly higher scores in the Openness and awareness and Interaction skills in nurses compared to GPs, while other research has reported no significant difference in cultural competence between professionals; however, sensitivity and knowledge regarding cultural competence were found to be higher in GPs compared to nurses (Pedrero et al, 2020).…”
Section: Discussioncontrasting
confidence: 77%
“…There seems to be a need of studies comparing cultural competence between different healthcare professionals. This study reported significantly higher scores in the Openness and awareness and Interaction skills in nurses compared to GPs, while other research has reported no significant difference in cultural competence between professionals; however, sensitivity and knowledge regarding cultural competence were found to be higher in GPs compared to nurses (Pedrero et al, 2020).…”
Section: Discussioncontrasting
confidence: 77%
“…Therefore, it is necessary to measure cultural competence and its impact on patients' treatment outcomes (Wang et al, 2018). To address this issue, several scales have been developed for measuring cultural competence; however, aspects associated with their psychometric properties remain unclear (Pedrero et al, 2020). Multiple instruments have been internationally developed to assess cultural competence (Jongen, McCalman & Bainbridge 2018;Jongen, Mc-Calman & Bainbridge 2017;Loftin et al, 2013;Rechel et al, 2013); however, it is not easy to choose the most appropriate instrument for a specific purpose (Purnell 2016).…”
Section: Introductionmentioning
confidence: 99%
“…El conocimiento cultural presenta la más alta puntuación, siendo superior a la reportada por Pedrero et al (2020) en profesionales de la salud en general y enfermeros en particular. Según esto, los estudiantes de Enfermería dan más valor al conocimiento relacionado con el impacto social, el estilo de comunicación, el conocimiento sobre los grupos con los que se está en contacto, la migración y el interés por comprender la diversidad cultural asociada a los cuidados de la salud (Pedrero, Bernales y Chepo, 2019).…”
Section: Discussionunclassified